2011
DOI: 10.1016/j.mcn.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

NFAT regulates pre-synaptic development and activity-dependent plasticity in Drosophila

Abstract: The calcium-regulated transcription factor NFAT is emerging as a key regulator of neuronal development and plasticity but precise cellular consequences of NFAT function remain poorly understood. Here, we report that the single Drosophila NFAT homolog is widely expressed in the nervous system including motor neurons and unexpectedly controls neural excitability. Likely due to this effect on excitability, NFAT regulates overall larval locomotion and both chronic and acute forms of activity-dependent plasticity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 60 publications
4
25
0
Order By: Relevance
“…However, our findings suggest the iav 1 and calcineurin mutant phenotypes studied here are unlikely to be NFAT dependent because NFAT knockouts display an increase in bouton number (Freeman et al, 2011) rather than the decrease observed in the iav 1 and calcineurin mutants. Thus, in the context of NMJ synapse development, calcineurin appears to function via Futsch rather than NFAT.…”
Section: Discussionmentioning
confidence: 55%
“…However, our findings suggest the iav 1 and calcineurin mutant phenotypes studied here are unlikely to be NFAT dependent because NFAT knockouts display an increase in bouton number (Freeman et al, 2011) rather than the decrease observed in the iav 1 and calcineurin mutants. Thus, in the context of NMJ synapse development, calcineurin appears to function via Futsch rather than NFAT.…”
Section: Discussionmentioning
confidence: 55%
“…Since the larval neuro-muscular system is simpler and experimentally more accessible than in the adult, we used this model synapse to test our idea. Baseline synaptic transmission was measured at the muscle 6/7 motor synapse in abdominal segment A2 in 1 mM external calcium as reported previously (Freeman et al, 2011; Sen et al, 2011). elav C155 -GAL4 was used to drive expression of full-length Smn or RNAi constructs as described in previous sections.…”
Section: Resultsmentioning
confidence: 99%
“…At the molecular level, NFAT-directed gene transcription regulates the expression of several key proteins critical for activity responses including IP 3 Rs, GluRs, and pro-nociceptive genes in neurons [102104]. Calcineurin-NFAT signaling is critical for neurotrophin-mediated axonal growth and guidance during vertebrate development [105,106] as well as presynaptic development [107], dendritogenesis [108], and neuronal survival [107110]. …”
Section: Physiological Roles Of Ca2+ Signaling In Neural Developmentmentioning
confidence: 99%